2014
DOI: 10.1371/journal.pone.0091881
|View full text |Cite
|
Sign up to set email alerts
|

Similar Resilience Attributes in Lakes with Different Management Practices

Abstract: Liming has been used extensively in Scandinavia and elsewhere since the 1970s to counteract the negative effects of acidification. Communities in limed lakes usually return to acidified conditions once liming is discontinued, suggesting that liming is unlikely to shift acidified lakes to a state equivalent to pre-acidification conditions that requires no further management intervention. While this suggests a low resilience of limed lakes, attributes that confer resilience have not been assessed, limiting our u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 76 publications
5
35
0
Order By: Relevance
“…For instance, Baho et al (2014) used time series modeling to determine the dominant temporal frequencies of phytoplankton dynamics in managed (liming to mitigate acidification effects) and unmanaged (acidified and circumneutral) lakes. They found that the temporal scaling patterns identified were due to dominant phytoplankton species, while rare species showed stochastic dynamics that were unrelated to the identified temporal scaling patterns.…”
Section: Adaptive Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Baho et al (2014) used time series modeling to determine the dominant temporal frequencies of phytoplankton dynamics in managed (liming to mitigate acidification effects) and unmanaged (acidified and circumneutral) lakes. They found that the temporal scaling patterns identified were due to dominant phytoplankton species, while rare species showed stochastic dynamics that were unrelated to the identified temporal scaling patterns.…”
Section: Adaptive Capacitymentioning
confidence: 99%
“…Most of the examples above highlight a community ecology focus of ecological resilience assessments, and these often scrutinize structural aspects of community composition and functional traits of specific taxonomic groups and how they are influenced by environmental factors (Truchy et al 2015). Targeting the quantification of some of these attributes using the structure of specific taxon groups was crucial to operationalizing the concept in terms of "resilience of what to what" ), e.g., the resilience of phytoplankton communities to liming (Baho et al 2014), or assessing the relative resilience of ecosystems by comparing resilience attributes of communities across sites (Allen et al 2005). However, resilience assessments based on specific taxon groups might not reflect the broader systemic or general resilience of an ecosystem, which would emanate from the broader interaction of all biological and environmental components, i.e., how an entire lake responds to interacting multiple stressors.…”
Section: A Hypothesis Framework Guiding Ecological Resilience Measurementioning
confidence: 99%
“…We acknowledge that in any assessment of resilience, numerically rare species can have a significant role (Angeler et al 2013b, Baho et al 2014. For instance, if abundant members of the same functional group are especially vulnerable to a particular disturbance, rare species with stochastic dynamics can potentially compensate for that loss and sustain important functions (Walker et al 1999).…”
Section: (E∩s)mentioning
confidence: 99%
“…Depending on the magnitude of the disturbance and the resilience of the respective ecosystem (i.e., the amount of disturbance an ecosystem can tolerate without changing its regime; Holling et al, 1973Holling et al, , 1986Scheffer and Carpenter, 2003;Baho et al, 2014), lake biota may react with extinction events and/or changes in community structures and functions.…”
mentioning
confidence: 99%